Reducing CO2 in the transport sector in Japan. (1st January 2001) - Yoshida, Yoshikuni; Ishitani, Hisashi; Matsuhashi, Ryuji; Kobayashi, Osamu; Takeishi, Tetsuo
In this paper, we have investigated the cost-effectiveness of alternative fuel vehicles as a measure for CO2 reduction. Computed results indicate that the installation of alternative fuel vehicles is much more expensive than fuel switching in industry or the power generation sector. However, some economic incentives will make the price go down to the level at which alternative fuel vehicles are competitive with conventional vehicles. At the same time, mass production makes their prices go down although it is rather expensive at present. Then, we developed the scenarios in which CO2 emissions could be stabilised at the level in 1990. In the higher demand case (1.2%/yr.), it is indispensable to introduce alternative fuel vehicles into the market. Our model selects electric vehicles and compressed natural gas vehicles as cost-effective options. In the scenario where carbon tax revenue is not offset by subsidy, we have to impose prohibitively high carbon tax to suppress CO2 . However, CO2 emission can be suppressed by a reasonable carbon tax if the tax revenue is returned to the market to subsidise alternative fuel vehicles and their infrastructures.